Job Satisfaction Can Mediate Between Work Culture and Work Motivation to Improve Employee Performance - Karo-karo, Alex P; Ongsa, Rezeki; Elisha, Elisha; Martinus, Martinus; W, Dennis; Anton, Anton (Newinera Publisher, 2024)
This research aims to determine the influence of work culture and work motivation on employee performance with job satisfaction as an intervening variable for PT employees. Ultra Adibangun Stella Perkasa Medan. This type of research is quantitative. The number of samples in this study was 92 respondents, the data analysis techniques used in this research were instrument testing (validity test and reliability test), classical assumption tests (normality, multicollinearity and heteroscedasticity), hypothesis testing (t test, F test and coefficient of determination) and path analysis test research models (Path Analysis). The results of this research show that 1) Work Culture has no effect on Job Satisfaction, 2) Work Motivation has a positive and significant effect on Job Satisfaction, 3) Work Culture has a positive and significant effect on Job Performance, 4) Work Motivation has a positive and significant effect on Employee Performance, 5) Job Satisfaction has no influence on Employee Performance, 6) Work Culture and Work Motivation simultaneously influence Employee Performance, 7) Work Culture influences Employee Performance through Job Satisfaction and 8) Work Motivation influences Employee Performance through Job Satisfaction.